Endoscopic Closure for Full-Thickness Gastrointestinal Defects: Available Applications and Emerging Innovations - Nobuyoshi Takeshita; Khek Yu Ho (Clinical Endoscopy, 2016)
Full-thickness gastrointestinal defects such as perforation, anastomotic leak, and fistula are severe conditions caused by various types of pathologies. They are more likely to require intensive care and a long hospital stay and have high rates of morbidity and mortality. After intentional full-thickness opening of hollow organs for natural orifice transluminal endoscopic surgery, safe and secure closure is urgently required. The currently available advanced endoscopic closing techniques have a major role in the treatment of full-thickness gastrointestinal defects. Appropriate usage of these techniques requires taking into account their advantages and limitations during practical application. We reviewed the available endoscopic modalities, including endoscopic clips, stents, vacuum-assisted closure, gap filling, and suturing devices, discussed their advantages and limitations when treating full-thickness gastrointestinal defects, and explored emerging innovations, including a novel endoluminal surgical platform for versatile suturing and a cell-laden scaffold for effective gap filling. Although these emerging technologies still require further pre-clinical and clinical trials to assess their feasibility and efficacy, the available modalities may be replaced and refined by these new techniques in the near future.